Sequencing and characterization of Helcococcus ovis: a comprehensive comparative genomic analysis of virulence - Federico Cunha; Segundo Casaro; Kristi L. Jones; Rafael S. Bisinotto; Subhashinie Kariyawasam; Mary B. Brown; Klibs N. Galvão (BMC Genomics, 2023)
Abstract Background Helcococcus ovis (H. ovis) is an emerging bacterial pathogen that commonly causes opportunistic respiratory, mammary, and uterine infections across mammalian hosts. This study applied long- and short-read whole genome sequencing technologies to identify virulence factors in five H. ovis isolates with low, medium, and high virulence phenotypes. Results The resulting assemblies contained one circular chromosome ranging from 1,744,566 to 1,850,083 bp in length and had a mean GC content of 27.6%. Phylogenetic and nucleotide identity analyses found low virulence strain KG38 to be part of a clade that forms an outgroup apart from the rest of the H. ovis taxon. Assembling the first complete genomes of the species revealed major genomic rearrangements in KG38. One to six prophage regions were identified in each genome. A novel pathogenicity island was found exclusively in the two high virulence strains (KG37 and KG104), along with two hypothetical transmembrane proteins designated as putative VFs. Finally, three zinc ABC transporters and three Type-II/IV secretion systems were identified as possible virulence determinants in this species. The low virulence strain KG38 has fewer intact paralogs of these operons in its genome compared to the higher virulence isolates, which strongly suggests a role in virulence. This strain is also missing four putative virulence factors (VFs) found in other isolates associated with adherence (collagen adhesin precursor), immune evasion (choline-binding protein A and a PspA-like hypothetical protein) and cell wall synthesis (glycerol-3-phosphate cytidylyltransferase). Conclusions In this study, we assembled reference-quality complete genomes for five H. ovis strains to identify putative virulence factors. Phylogenetic analyses of H. ovis isolates revealed the presence of a clade representing a potentially novel species within the genus Helcococcus. A novel pathogenicity island and two hypothetical transmembrane proteins were found exclusively in high-virulence strains. The identification of Zinc ABC transporters and Type-II/IV secretion systems as possible virulence determinants, along with the differences in operon content between the low and high virulence isolates, strongly suggests they also play a role in the bacterium’s pathogenicity. Taken together, these findings are a valuable first step toward deciphering the pathogenesis of H. ovis infections.